BRS FS311: common bean cultivar with striped seed coat, high yield, and commercial quality - Aguiar,Marcelo Sfeir de (2021)
Abstract BRS FS311 is a cultivar of common bean in the striped seed coat group, with high yield, larger bean grain, and visual appearance suitable for the striped seed coat standard. It also has a cycle of semi-early, upright architecture and moderate resistance to fusarium wilt and anthracnose.